Assessment of economically attractive low-carbon solutions across India's transport, building and agriculture sectors - Shandelle Steadman; Elizabeth Tan; Laetitia Pettinotti; Tony Mwenda Kamninga; Vir Ahlawat; Sanjana Kapoor; Aatif Somji; Upasna Handa (ODI, 2024)
In emerging market and developing economies such as India, significant mobilisation of private capital is necessary to meet climate targets and shift to a low carbon development pathway. However, one barrier to unlocking this investment is a lack of well-identified investment opportunities. In this report we generate evidence that could help address this by conducting an assessment of the cost and carbon saving potential of a wide range of low-carbon measures which could be adopted in the Indian transport, building and agriculture sectors by 2030 instead of their traditional business as usual alternative. India presents a vast opportunity for cost-effective, low-carbon investments in transport, building, and agriculture. By prioritising electric vehicles, energy-efficient buildings, and sustainable agricultural practices, India can significantly reduce emissions and save billions of rupees. Electric vehicles, particularly light-duty trucks, offer substantial cost savings and emissions reductions in the transport sector. In the building sector, cool roofs and energy-efficient designs can improve building performance and reduce energy consumption. Sustainable farming practices, such as zero-till cultivation and solar-powered irrigation, can enhance agricultural productivity and reduce environmental impact in the agriculture sector. By investing in these low-carbon solutions, India can achieve its ambitious climate targets, boost economic growth, and improve air quality and public health.
Keywords: 330; Economic transformation; Economic growth; Energy; India